2020
DOI: 10.1093/jas/skaa318
|View full text |Cite
|
Sign up to set email alerts
|

Xylanase supplementation in corn-based swine diets: a review with emphasis on potential mechanisms of action

Abstract: Corn is a common energy source in pig diets globally; when financially warranted, industrial corn co-products, such as corn distiller’s dried grains with solubles (DDGS), are also employed. The energy provided by corn stems largely from starch, with some contribution from protein, fat, and non-starch polysaccharides (NSP). When corn DDGS are used in the diet, it will reduce starch within the diet, increase dietary protein, fat, and NSP levels, and alter the source profile of dietary energy. Arabinoxylans compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 97 publications
0
38
0
Order By: Relevance
“…There are contradicting reports on the efficacy of xylanase to improve nutrient and energy digestibility, fermentation, and growth performance in growing pigs ( Torres-Pitarch et al, 2019 ; Petry and Patience, 2020 ). These inconsistencies could be due to differences in enzyme characteristics, inadequate supplementation time, dietary fiber concentration, or the physicochemical properties of insoluble corn-based fiber ( Petry and Patience, 2020 ). Additionally, results of recent research suggest at least 25 d of adaptation may be needed for xylanase to improve fiber digestibility in the upper small intestine of pigs fed corn-based fiber ( Petry et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are contradicting reports on the efficacy of xylanase to improve nutrient and energy digestibility, fermentation, and growth performance in growing pigs ( Torres-Pitarch et al, 2019 ; Petry and Patience, 2020 ). These inconsistencies could be due to differences in enzyme characteristics, inadequate supplementation time, dietary fiber concentration, or the physicochemical properties of insoluble corn-based fiber ( Petry and Patience, 2020 ). Additionally, results of recent research suggest at least 25 d of adaptation may be needed for xylanase to improve fiber digestibility in the upper small intestine of pigs fed corn-based fiber ( Petry et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, there is evidence to suggest supplementing xylanase increases fiber solubility in the ileum ( Tiwari et al, 2018 ), and this soluble NSP fraction in the ileal effluent may subsequently alter digesta viscosity in the large intestine. However, the efficacy of xylanase in pigs fed corn-based diets is variable and not fully understood ( Petry and Patience, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial fermentation largely occurs in the cecum and colon due to the dense microbial populations in these gastrointestinal regions ( Jensen and Jørgensen, 1994 ). Additionally, there are increasing reports that supplementation of xylanase to swine benefits markers of improved gastrointestinal health, and commonly reduces finishing pig mortality in commercial production ( Petry and Patience, 2020 ). These improvements in health are often postulated to result from modulation of microbial populations in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that these AXOS can be rapidly fermented by the resident microbiota and modulate the gastrointestinal microbiota in the large intestine of poultry via a stimbiotic MOA ( Bautil et al, 2020 ; González-Ortiz et al, 2020 ). However, there is a dearth of research in swine ( Petry and Patience, 2020 ). A stimbiotic was defined by González-Ortiz et al (2019) , as “ an additive that stimulates a fiber-degrading microbiome resulting in an increase in fiber fermentability even though the additive itself contributes little to short chain fatty acid production .” The proposed mechanism of a stimbiotic is that it accelerates the capacity of the large intestine to more efficiently digest fiber by modulating microbial taxa that produce their own carbohydrases ( Bautil et al, 2020 ; González-Ortiz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, endo-xylanase, and exo-xylanase are the most important contributors to xylan depolymerization. Until now, vast applications of xylanase have been extensively explored based on its ability in xylan degradation, for example, biofuels production [ 6 , 7 , 8 ], pulp and paper bleaching [ 9 , 10 , 11 ], bioactive compounds [ 12 , 13 , 14 ], animal feed [ 15 , 16 ], and baking [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%